Who, Where, When, and How? Challenges for Prediction and Control of Forest Damage - Valentyna Meshkova (Environmental Sciences Proceedings, 2022)
The purpose of the research was to combine our own data and the published data from forests in Ukraine on the approaches for improving the prediction and control of forest insect pests. Climate change and anthropogenic activity bring changes in forest structure, its vulnerability to pests, pest species composition, and harm. The most dangerous alien species are Leptoglossus occidentalis, Corythucha arcuata, and Agrilus planipennis. Forecasts should consider contemporary pest composition, seasonal development, harm, the area and structure of vulnerable forests, and foliage mass depending on the natural zone, tree health condition, and additional damaging factors.